Intranasal Ketamine for Acute Pain: Behavioral and Neurophysiological Safety Analysis in Mice - Nidhi Goswami, M.Sc; Mohd Aleem, M.Sc; Kailash Manda, Ph.D (Elsevier, 2021)
ABSTRACT: Background: Subanesthetic ketamine has been used for treatment-resistant depression and is popular as an opioid-sparing agent. Objective: The present study aimed to investigate the dose-dependent antinociceptive effect of intranasal ketamine (INK) along with behavioral and neurophysiological safety in mice. Methods: Antinociceptive efficacy was evaluated in the terms of thermal nociceptive response and formalin test. The safety studies were carried out separately in healthy mice using telemetry-based cortical electroencephalography, hemodynamic changes, and spontaneous behavioral functions, including anxiety, stereotypic movement, and locomotor functions. Results: INK administration significantly augmented the thermal nociceptive threshold and alleviated the pain response in the tonic phase of the formalin test. The results showed the dose-independent effectiveness of ketamine for thermal nociceptive responses because there were no significant differences among different INK dose groups. Behavioral safety analysis using the open field exploratory test revealed no significant effect of INK on anxiety-like functions in healthy mice. However, INK mice showed significantly more stereotypic movement but slower locomotor activities. The electroencephalography signal power spectrum density analysis revealed no significant changes by INK administration except a lower value in the α range. No significant changes were reported in heart rate, diastolic blood pressure, or systolic blood pressure at the higher dose equivalent used in the pain model. Conclusions: The study demonstrated the behavioral and neurophysiological safety of INK, although it had a mild sedative effect. Therefore, INK is suggested as a potentially safe candidate for the management of acute pain. (Curr Ther Res Clin Exp. 2021; 82:XXX-XXX)© 2021 Elsevier HS Journals, Inc.